Computational statistics in data science - Zhang, Hao Helen; Lee, Thomas C. M.; Piegorsch, Walter W.; 1969- Levine, Richard A. (Wiley, 2022)
The Wiley Handbook of Statistical Computing will provide a compendium of concepts, theories, techniques, and practices in statistical computing for users desiring a single, standalone sourcebook for this important area of contemporary data science. The Handbook will contain a series of sub-sections, each devoted to a central arena of statistical computing within which external authors -- including the co-Editors -- offer modern presentations on specific topical areas. Finalized entries in the new Handbook will also be available in Wiley StatsRef: Statistics Reference Online compendium, helping to build the source base for Wiley StatsRef while also providing authors with the opportunity to showcase their work in multiple locations for maximal impact"--